KAIZEN 5'S INDUSTRIAL WORK CULTURE-BASED SCHOOL FACILITIES AND INFRASTRUCTURE MANAGEMENT MODEL'S SUSTAINABLE DEVELOPMENT GOALS (SDGS) AT STATE VOCATIONAL SCHOOLS IN THE BIREUEN REGENCY - Azhari; Arif Rahman; Aman Simaremare; Yuniarto Mudjisusatyo; Kisno; Sherly (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Introduction: An essential part of Indonesia's National Education Standards are the infrastructure and facilities for education. All formal and informal educational institutions are required to provide facilities that assist students' physical, intellectual, social, emotional, and psychological development, as stipulated in Article 45 of the National Education System Law No. 20 of 2003. Objective: In order to create a school facilities and infrastructure management model that is focused on the Sustainable Development Goals (SDGs), this project will integrate the 5S Kaizen industrial work culture into vocational schools (SMK Negeri) in the Bireuen Regency. It also assesses how useful and successful the model is at streamlining school facility management. Method: The study used Plomp's model as part of its Research & Development (R&D) process, which consisted of five stages: analysis, design, development, implementation, and assessment. Principals, vice principals, heads of expertise programs, workshop leaders, administrative leaders, and effective teachers were among the participants. Validated by expert evaluations, implementation observations, response surveys, and competency tests, the research tools included a model book, an implementation manual, and a module guide. Results: The average validation scores for the generated model were 4.57 (model), 4.62 (implementation handbook), and 4.63 (module guide), indicating strong validity. Positive participant response rates in trials I and II were 85.91% and 86.31%, respectively, indicating that classical completeness was attained. The N-Gain analysis classified its effectiveness as moderate, showing competency gains of 61.75% and 62.21%. Conclusion: The model promotes ongoing advancement in vocational education by encouraging an organized, industry-based approach to SDG-aligned school facility management. For policymakers and school administrators working in vocational education settings, this study offers a novel paradigm for incorporating industrial methodologies—specifically, 5S Kaizen—into the administration of educational infrastructure.